Aru Shah and the city of gold - Chokshi, Roshani (Chokshi, Roshani. Pandava novel, 2022)
With no memory of the wish she made on the tree of wishes, Aru Shah increasingly doesn't trust the fickle gods and questions whether she should fight on behalf of the devas against the Sleeper and his demon army.